2004
DOI: 10.1007/s00068-004-1340-x
|View full text |Cite
|
Sign up to set email alerts
|

Trauma and Fracture of the Mandible

Abstract: Background: The mandible is one of the most frequently fractured bones. The objective of this prospective study was to determine and illustrate fracture patterns of the mandible in relation to various etiologic factors. Patients and Methods: A total of 218 patients with mandibular fractures were included in this study. Data regarding age, gender, causes and anatomic sites of fractures and treatment modalities were collected. Conventional plain radiographs of the mandible were obtained in all patients. The plai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
2
1
1
Order By: Relevance
“…However, it was similarly observed that road traffic crash was the leading cause of the maxillofacial hard tissue injuries that presented at KATH. This was in contrast to a study by Copcu E and colleagues [30] who demonstrated that assault victims had a higher frequency of angle fractures;…”
Section: Discussioncontrasting
confidence: 98%
“…However, it was similarly observed that road traffic crash was the leading cause of the maxillofacial hard tissue injuries that presented at KATH. This was in contrast to a study by Copcu E and colleagues [30] who demonstrated that assault victims had a higher frequency of angle fractures;…”
Section: Discussioncontrasting
confidence: 98%
“…Fracture morphology depends on the aetiology and patient factors. In humans, patient factors depend mainly on anatomical characteristics like the relative strength of certain regions of the bone, size and shape of the bone, and muscle attachments (4). Fracture morphology also depends on the characteristics of the force such as direction, rate, amount and nature, as well as the spatial relationship of the bone to the force (4).…”
Section: Introductionmentioning
confidence: 99%
“…Combined craniomaxillofacial (CMF) and orthopedictraumatological (OT) injuries are common and pose a challenge to traumatological teams in the emergency unit. These injuries predominantly result from assaults and high energy traumata like traffic accidents [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%